The effect of landing type on kinematics and kinetics during single-leg landings - Hovey, S.; Wang, H.; Judge, L. W.; Avedesian, J. M.; Dickin, D. C. (Sports Biomechanics, 2021)
Landing research attempts to simulate sport activities; however, movements performed pre- or post-landing may alter landing mechanics and injury risk. Therefore, this study compared lower extremity biomechanics of single-leg drop landings, drop jump (DJ) and countermovement jump (CMJ) landings as well as sex-related differences. A total of 25 recreational athletes (11 females) performed landings from 80% maximum jump height with impact forces, kinematics and joint moments measured during each landing. Altered kinematic and kinetic variables were revealed when a jump was performed pre- or post-landing. CMJ landings were generally performed with a more extended lower extremity at ground contact, less hip and knee motion in the frontal and transverse planes and larger joint moments compared to other landings (p < 0.01). The DJ landings demonstrated greater joint flexion and large frontal and transverse plane motion, paired with decreased impact forces and joint moments (p < 0.05). Across all landings, males displayed larger impact forces and joint moments (p < 0.01), and females demonstrated frontal plane kinematics associated with increased injury risk (p < 0.05). These findings suggest that activities surrounding the landing directly impact landing mechanics and overall risk. Therefore, matching landing type to sport-specific activities increases the efficacy of assessing injury risk during training or rehabilitation programmes.